Expected performances of the NOMAD/ExoMars instrument. (May 2016) - Robert, S.; Vandaele, A.C.; Thomas, I.; Willame, Y.; Daerden, F.; Delanoye, S.; Depiesse, C.; Drummond, R.; Neefs, E.; Neary, L.; Ristic, B.; Mason, J.; et al.
Abstract: NOMAD (Nadir and Occultation for MArs Discovery) is one of the four instruments on board the ExoMars Trace Gas Orbiter, scheduled for launch in March 2016. It consists of a suite of three high-resolution spectrometers – SO (Solar Occultation), LNO (Limb, Nadir and Occultation) and UVIS (Ultraviolet and Visible Spectrometer). Based upon the characteristics of the channels and the values of Signal-to-Noise Ratio obtained from radiometric models discussed in (Vandaele et al., 2015a, 2015b ;Thomas et al., 2016 ), the expected performances of the instrument in terms of sensitivity to detection have been investigated. The analysis led to the determination of detection limits for 18 molecules, namely CO, H2 O, HDO, C2 H2, C2 H4, C2 H6, H2 CO, CH4, SO2, H2 S, HCl, HCN, HO2, NH3, N2 O, NO2, OCS, O3 . NOMAD should have the ability to measure methane concentrations <25 parts per trillion (ppt) in solar occultation mode, and 11 parts per billion in nadir mode. Occultation detections as low as 10 ppt could be made if spectra are averaged (Drummond et al., 2011 ). Results have been obtained for all three channels in nadir and in solar occultation. Highlights: A sensitivity study of the NOMAD instrument has been performed. The analysis led to the determination of detection limits for 18 molecules. Methane concentrations <25 ppt may be detected in solar occultation mode. Abundances as low as 11 ppb of methane may be detected in nadir mode.